Anorexia nervosa during COVID-19: loss of personal control and alexithymia as important contributors to symptomatology in adolescent girls - Irina Jarvers; Angelika Ecker; Daniel Schleicher; Stephanie Kandsperger; Alexandra Otto; Romuald Brunner (Journal of Eating Disorders, 2023)
Abstract Background In the course of the COVID-19 pandemic, a steady increase in adolescent anorexia nervosa admissions has been observed. Contributing factors may have been uncontrollable changes in school attendance due to lockdowns and social restrictions. However, patients’ reports on the impact of these factors have not been assessed in detail as of yet. Furthermore, alexithymia, the difficulty to identify and describe one’s own emotions, has increased during the pandemic and is known to be heightened in eating disorders. Thus, it may have contributed to symptom severity in anorexia nervosa during the pandemic. Methods The present study examined pandemic-related changes in social media use, body satisfaction, and perceived loss of control and their impact on depressive, anxious, and eating disorder symptomatology in a sample of adolescent girls with anorexia nervosa (n = 29) and healthy controls (n = 23). Additionally, the influence of current alexithymia as a cross-diagnostic risk factor was assessed. Adolescents answered questionnaires once shortly after admission to inpatient, outpatient, or daycare treatment. Results An increase in perceived loss of control during the pandemic and heightened alexithymia explained a significant portion of variance in present depressive symptomatology, which in turn contributed to eating disorder symptomatology. Conclusions These relationships emphasize alexithymia and perceived loss of control as valuable constructs for early screenings and interventions.